Penguatan Karakter dan Kesadaran Sosial melalui Program Desa Berbasis Nilai - Abdullah KhoitsamahAssilmi; Toha Toniawan; Eliya Eliya; Zuyyinah Awwaliyyah; Farhan Farhan (Jurnal Pendidikan Educandum, 2026)
This community service program aims to strengthen character formation and social awareness through a value-based village development model integrating ecological responsibility, public safety, Qur’anic literacy, and higher education aspiration. The program was implemented using a participatory action research approach involving youth groups, religious leaders, and local residents. Activities included the Zero Waste movement through a waste bank initiative, the No Accident reflector installation program, Ramadan religious parade activities, TBQ (Tebar Berkah Al-Qur’an) for Qur’anic literacy improvement, and the Saya Siap Kuliah educational motivation expo. Data were collected through observation, interviews, documentation, and reflective evaluation. The results indicate increased community participation in environmental management, improved public safety awareness, strengthened Qur’anic reading competence among children and adolescents, and higher motivation to pursue tertiary education. The integration of ecological, social, and religious values demonstrates that community-based value education can function as a sustainable model for strengthening village character and collective responsibility.